Relationship Between Organizational Culture And Innovativeness Of Public Listed Housing Developers - Yusof , Nor'Aini; Abu-Jarad, Ismael (2011)
The benefits of innovation and the need to be innovative have been highlighted by many. However, it is doubtful whether the players in the housing industry, in particular the housing development firms, have the characteristics that are favourable for innovation. The study seeks to examine the relationship between organizational culture and innovativeness of public-listed housing developers in Malaysia. A survey was conducted to all housing developers that were registered with the Bursa Malaysia. The data were analyzed using descriptive statistics, reliability test and correlation analysis. The results revealed that 4 out of 8 dimensions of the organizational culture were statistically significant with organizational innovativeness with moderate strength. Specifically, performance orientation, humanitarian and assertiveness culture had highly significant relationships with organizational innovativeness while future orientation had a significant relationship with organizational innovativeness.